2013
DOI: 10.1093/ajh/hpt215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bariatric Surgery on Cardiac Structure and Function: A Systematic Review and Meta-Analysis

Abstract: The present meta-analysis, the largest to date focusing on cardiac structural and functional changes in morbidly obese subjects after bariatric surgery, documents that this therapeutic approach exerts important cardioprotective effects in terms of regression of LV hypertrophy, improvement of LV geometry and diastolic function, and reduction of left atrial size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 47 publications
4
55
1
3
Order By: Relevance
“…In a study of 727 young-to-middle age, untreated subjects screened for stage 1 hypertension and followed up for 8 years, obesity was associated with both incident sustained hypertension and LVH. 29 There is also scattered evidence that reduction of body mass index has favorable effects on reduction of LVH 30,31 and that LVH is a distinctive characteristics in metabolic syndrome even in the absence of arterial hypertension. 32 In the context of a population of hypertensive patients, obesity is a deleterious condition, substantially increasing the chance to develop LVH.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 727 young-to-middle age, untreated subjects screened for stage 1 hypertension and followed up for 8 years, obesity was associated with both incident sustained hypertension and LVH. 29 There is also scattered evidence that reduction of body mass index has favorable effects on reduction of LVH 30,31 and that LVH is a distinctive characteristics in metabolic syndrome even in the absence of arterial hypertension. 32 In the context of a population of hypertensive patients, obesity is a deleterious condition, substantially increasing the chance to develop LVH.…”
Section: Discussionmentioning
confidence: 99%
“…2 Finally, we and others have found that adolescents undergoing WLS had evidence of a pathologic impact of severe obesity on cardiac structure and physiology (ie, diastolic dysfunction and elevated cardiac workload). 27,30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Weight loss, however achieved, has been shown to result in improved LV systolic and diastolic function [31]. In a study of 261 patients with BMI ≥ 30 kg/m 2 who undertook a behavioural intervention programme including dietary restriction and exercise training, independent predictors of improvement in LV function were weight reduction, improvement in insulin resistance and absence of diabetes [32].…”
Section: Discussionmentioning
confidence: 99%